Achieving cost optimization via effective procurement process governance: a case study of Japan Vietnam Petroleum Company (JVPC) - Tran, Xuan Thuy; Huynh, Trung Luong; Swierczek, F.W.; Thitos Laosirihongthong; Japan Vietnam Petroleum Company (Pathumthani : Asian Institute of Technology, 2015)
Japan Vietnam Petroleum Company, on behalf of its partners, has been operating the oil field in the Block 15-2 offshore Vietnam since 1992 in the safest and most effective manner that significantly benefits all parties. In recent years, the production volume is coming down but maintenance & operation costs still increases. Besides that the oil price is sharply decreased during this period and forecasted to remain low in this year and next few years. JVPC{u2019}s Management is being strongly requested by its partners to cut off maintenance costs and optimize its operational expenditures. As a Procurement Officer of Contract and Procurement Group, the author actually wants to conduct this research in order to study and identify the major factors and reasons why and what cause higher costs to the company. Some well-known business analysis methods have been used in this research to analyze the company{u2019}s business environment. Such as 7s McKinsey model, SWOT. The author{u2019}s observation and experience are also used to support the research issues. The author has also conducted a questionnaire survey with the related people who got involved in the procurement process. Organization behavior such as satisfactions, motivation, leadership, conflict, negotiation, organization structure & culture, human resource policies and organization change as well as stress management have also been discussed and analyzed. The results of this research could be proposed to the company management board for review and consideration and then issuing appropriate measures to change and improve where necessary in order to help the company to reduce as much as possible.
A project submitted in partial fulfillment of the requirements for the degree of Master of Business Administration (Executive) in International Business {u2013} Management of Technology (VN), School of Management
Keywords: Japan Vietnam Petroleum Company; Costs; Optimization